The impact of a change in prescribing policy on antipsychotic prescribing in a general adult psychiatric hospital. (9th May 2014) - Kelly, J.; Kelly, F.; Santlal, K.; O'Ceallaigh, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives To examine the impact of a change in local prescribing policy on the adherence to evidence-based prescribing guidelines for antipsychotic medication in a general adult psychiatric hospital. Methods All adult in-patients had their clinical record and medication sheet reviewed. Antipsychotic prescribed, dose prescribed and documented indications for prescribing were recorded. This was done before and after the implementation of the change in hospital antipsychotic prescribing policy. Results There were no significant differences in age, sex, Mental Health Act status, psychiatric diagnosis or documented indications for prescribing multiple or high dose antipsychotics between the two groups. There was an increase in the preferential prescribing of multiple second-generation antipsychotics (p=0.01) in the context of a significant reduction in the prescribing of multiple antipsychotics overall (p=0.02). There were no significant reductions in prescribing of mixed generations of antipsychotics (p=0.12), high dose antipsychotics (p=1.00) or as required (PRN) antipsychotics (p=0.74). Conclusions Changes in local prescribing policy can improve adherence to quality prescribing guidelines and cause clinically significant improvements in patterns of prescribing in a general adult psychiatric hospital.